2016
DOI: 10.1016/j.afos.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of spinal cord injury on bone loss and dysregulation of the calcium/parathyroid hormone loop in mice

Abstract: ObjectiveTo map the progression of osteoporosis following spinal cord injury in mice in specific areas and analyze changes in parathyroid hormone (PTH) and ion levels which could be responsible for overall bone loss.Summary of background dataSpinal cord injury rapidly induces severe bone loss compared to other conditions, yet the cause of this bone loss has not been identified. Studies suggest the bone loss after injury is not solely due to disuse.MethodsTo quantify bone loss we weighed individual bones and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Specifically, SCI results in to rapid reduction of sublesional cancellous bone mass [e.g., BMD and bone volume (BV/TV)] as well as deleterious microarchitectural changes (e.g., increased Tb.Sp and higher SMI for rod-like geometry, as well as reduced Tb.N, Conn.D and stiffness), indicative of compromised structural integrity and reduced mechanical strength. These skeletal deficits due to SCI become more evident at 7 days, which is consistent with the previous findings [10][11][12]. The rapid decline in bone mass and deterioration of bone microstructure highlight a clinical need that any intervention for the prevention of bone loss after the acute event should start as soon as possible after paralysis and immobilization.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Specifically, SCI results in to rapid reduction of sublesional cancellous bone mass [e.g., BMD and bone volume (BV/TV)] as well as deleterious microarchitectural changes (e.g., increased Tb.Sp and higher SMI for rod-like geometry, as well as reduced Tb.N, Conn.D and stiffness), indicative of compromised structural integrity and reduced mechanical strength. These skeletal deficits due to SCI become more evident at 7 days, which is consistent with the previous findings [10][11][12]. The rapid decline in bone mass and deterioration of bone microstructure highlight a clinical need that any intervention for the prevention of bone loss after the acute event should start as soon as possible after paralysis and immobilization.…”
Section: Discussionsupporting
confidence: 89%
“…We previously showed that substantial loss of bone mineral content and bone volume was found for the distal femur and proximal tibia of rats at 56 days after spinal cord transection [24,25,27,28]. Recent studies demonstrated that SCI causes bone loss and deterioration of trabecular bone microstructure at 10 days [9] or even as early as 1 week [10][11][12] after injury. The present study is the first to report that bone loss and deterioration of trabecular bone microstructure occur as early as 2 days after neurologically motor-complete SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first phase is characterized by rapid bone reabsorption, which plateaus 18–24 months post-injury. The second chronic phase is characterized by gradual bone loss and inhibited bone formation [ 9 , 10 ]. As a result, about 40% of individuals with chronic SCI experience fractures; thus, twice the likelihood of fracture formation compared to individuals without SCI [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, decreased gas exchange and nutrient delivery promotes local hyperpressure and increased stimulation of osteoclasts. Significant bone resorption and demineralization also occurs [ 10 , 11 ]. This mechanism suggests a link between neural and physiological disorders in the pathogenesis of bone loss [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%